Preparation and Study of Some Mn(II), Co(II), Ni(II), Cu(II), Cd(II) and Pb(II) Complexes Containing Heterocyclic Nitrogen Donor Ligands - Shayma A. Shaker (E-Journal of Chemistry)
This paper presents a new mixed-ligand complexes with the general formula [M(BT)(BI)2X2] where BT=benzotriazole, BI=benzimidazole, X=SCN and M=Mn(II), Co(II), Ni(II), Cu(II), Cd(II) and Pb(II). The reaction was carried out by using the appropriate molar ratios of metal:ligand (1:1:2:2) (M:BT:BI:X) as required. The resulting products were found to be solids, not soluble in water and in ordinary organic solvents but highly soluble in DMSO. These complexes have been studied by UV-visible, IR and (1H, 13C) NMR spectra, molar conductivity, elemental analysis of C, H, N, determination of metal and magnetic susceptibility. The result suggests that the benzimidazoleas as a monodentate was coordinated with the metal ions through the N atom. Nevertheless, the benzotriazole as bidentate was coordinated with the metal ions through the N2 and N3 atoms. SCN was coordinated with the metal ions through the nitogen atom.